Persistent and extended COVID, post-COVID-19. New reflections in 2024 - Alfredo Darío Espinosa Brito (Medisur)
The world was shaken when the COVID-19 pandemic appeared. Unlike previous events, a new and nebulous epidemic is sweeping the universe: long COVID, or post-COVID-19 (Long COVID or Post-COVID Syndrome). Its definition as a “new disease” is very complicated due to the polymorphism of the clinical manifestations of patients and their changing profile in different scenarios, with the presence of numerous subjective symptoms. There is no solid evidence of its detailed pathogenesis, nor tests that confirm or rule out its diagnosis. Although most therapeutic approaches in patients with persistent COVID are symptomatic and supportive, based on the clinical expertise of the professionals who care for the patients, recent advances in the description of clinical phenotypes, further research into molecular research and the search to identify specific biomarkers could provide new evidence on their pathogenic mechanisms and more personalized approaches to the clinical care of these patients, who constitute a real health and occupational problem in the world today. It is therefore important to pay increasing attention to research on post-infectious syndromes, present and future, and not to neglect their importance in applying them for the benefit of those affected.